2012
DOI: 10.1002/eji.201142350
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel glycolipid ligands activating a sulfatide‐reactive, CD1d‐restricted, type II natural killer T lymphocyte

Abstract: Sulfatide-reactive CD1d-restricted natural killer T (NKT) lymphocytes belong to the type II NKT cell subset with diverse TCRs, and have been found to regulate experimental autoimmune encephalomyelitis, tumor immunity, and experimental hepatitis in murine models. NKT cells can be activated by self-lipids presented by CD1d, manifested as autoreactivity. The identity of most of these self-lipids remains unknown. By isolating lipids from a CD1d-expressing, highly stimulatory antigen presenting cell, we identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 41 publications
2
44
1
Order By: Relevance
“…Previous studies with type II NKT cell hybridomas have identified several self-lipid antigens recognized by type II NKT cells, including phospholipids, β-GlcCer, and sulfatide (27,(36)(37)(38)(39)(40). Interestingly, we found that 4get + type II NKT cells are potently activated by β-GlcCer containing C12:0 and C24:1 acyl chains, suggesting that a significant proportion of type II NKT cells recognize β-GlcCer.…”
Section: Tcrβmentioning
confidence: 49%
“…Previous studies with type II NKT cell hybridomas have identified several self-lipid antigens recognized by type II NKT cells, including phospholipids, β-GlcCer, and sulfatide (27,(36)(37)(38)(39)(40). Interestingly, we found that 4get + type II NKT cells are potently activated by β-GlcCer containing C12:0 and C24:1 acyl chains, suggesting that a significant proportion of type II NKT cells recognize β-GlcCer.…”
Section: Tcrβmentioning
confidence: 49%
“…Indeed, dNKT cells do not recognize α-GalCer or any of the α-glycan-linked microbial lipid antigens that are recognized by iNKT cells, and the selflipid sulfatide, which is recognized by a small subset of mouse dNKT cells, is not recognized by iNKT cells (9,10). Furthermore, the self-antigen β-GluCer, which stimulates most or all human and mouse iNKT cells, stimulates only a small subset of mouse dNKT cells (11,12). A number of studies have documented, or inferred, a function for dNKT cells during infection (13,14), yet the antigens that stimulate dNKT cells during infection remain unknown.…”
mentioning
confidence: 99%
“…Food Technol., Campinas, v. 19, e2016047, 2016 Recent advances in food allergy Alcocer, M. J. C. et al cell CAUBET et al, 2014). The majority of NKT cells express highly restricted TCRs with an invariant α-chain (Vα24-Jα18 in humans and Vα14-Jα18 in mice) and limited β-chains, therefore they are referred to as Type I or invariant NKT cells (iNKT) (PEI et al, 2011;RHOST et al, 2012). Type II cells form the remaining NKT cells and express non-invariant TCRs.…”
Section: Other Il-inducing Cellsmentioning
confidence: 99%